Validation of Risk Prediction Models to Detect Asymptomatic Carotid Stenosis. Issue 8 (21st April 2020) - Poorthuis, Michiel H. F.; Halliday, Alison; Massa, M. Sofia; Sherliker, Paul; Clack, Rachel; Morris, Dylan R.; Clarke, Robert; de Borst, Gert J.; Bulbulia, Richard; Lewington, Sarah
Abstract : Background: Significant asymptomatic carotid stenosis (ACS) is associated with higher risk of strokes. While the prevalence of moderate and severe ACS is low in the general population, prediction models may allow identification of individuals at increased risk, thereby enabling targeted screening. We identified established prediction models for ACS and externally validated them in a large screening population. Methods and Results: Prediction models for prevalent cases with ≥50% ACS were identified in a systematic review (975 studies reviewed and 6 prediction models identified [3 for moderate and 3 for severe ACS]) and then validated using data from 596 469 individuals who attended commercial vascular screening clinics in the United States and United Kingdom. We assessed discrimination and calibration. In the validation cohort, 11 178 (1.87%) participants had ≥50% ACS and 2033 (0.34%) had ≥70% ACS. The best model included age, sex, smoking, hypertension, hypercholesterolemia, diabetes mellitus, vascular and cerebrovascular disease, measured blood pressure, and blood lipids. The area under the receiver operating characteristic curve for this model was 0.75 (95% CI, 0.74–0.75) for ≥50% ACS and 0.78 (95% CI, 0.77–0.79) for ≥70% ACS. The prevalence of ≥50% ACS in the highest decile of risk was 6.51%, and 1.42% for ≥70% ACS. Targeted screening of the 10% highest risk identified 35% of cases with ≥50% ACS and 42% of cases with ≥70% ACS. Conclusions: Individuals at high risk of significant ACS can be selected reliably using a prediction model. The best‐performing prediction models identified over one third of all cases by targeted screening of individuals in the highest decile of risk only.